The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0195816
|View full text |Cite
|
Sign up to set email alerts
|

Automated and real-time segmentation of suspicious breast masses using convolutional neural network

Abstract: In this work, a computer-aided tool for detection was developed to segment breast masses from clinical ultrasound (US) scans. The underlying Multi U-net algorithm is based on convolutional neural networks. Under the Mayo Clinic Institutional Review Board protocol, a prospective study of the automatic segmentation of suspicious breast masses was performed. The cohort consisted of 258 female patients who were clinically identified with suspicious breast masses and underwent clinical US scan and breast biopsy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…To perform the segmentation task, we chose a U-net-like architecture implemented in the fast.ai library 6 . U-net was developed specifically for semantic segmentation and has been successfully applied to complex biomedical images such as electron microscopy of neuronal structures and MRI or ultrasound images in breast cancer screening 9,12,13 . We trained the U-net network using 492 plate images and corresponding Ilastik-generated masks, with 20% kept aside for validation (see Implementation for full training parameters).…”
Section: Resultsmentioning
confidence: 99%
“…To perform the segmentation task, we chose a U-net-like architecture implemented in the fast.ai library 6 . U-net was developed specifically for semantic segmentation and has been successfully applied to complex biomedical images such as electron microscopy of neuronal structures and MRI or ultrasound images in breast cancer screening 9,12,13 . We trained the U-net network using 492 plate images and corresponding Ilastik-generated masks, with 20% kept aside for validation (see Implementation for full training parameters).…”
Section: Resultsmentioning
confidence: 99%
“…Rodrigues et al [20] took the advantage of pixel-wise classification and achieved a DSC of 0.824. Kumar et al [21] proposed convolutional neural network approaches for breast ultrasound lesion segmentation and their algorithms effectively segmented the breast masses, achieving a mean DSC of 0.82.…”
Section: Fig 1 a Malignant Lesion In Breast Ultrasoundmentioning
confidence: 99%
“…This model achieved a similar sensitivity, positive predictive value, negative predictive value, and accuracy for the diagnosis of malignant thyroid tumors with higher specificity compared to those corresponding to experienced radiologists ( 12 , 13 ). For the detection of breast cancer, Kumar et al reported a real-time segmentation model of breast tumors using a CNN ( 14 ). This system can reportedly segment tumor images in real-time, suggesting its potential for clinical applications.…”
Section: History and Recent Progress Of Ai In Medical Imagingmentioning
confidence: 99%